METHODS OF USING NATIONAL MUSICAL INSTRUMENTS IN MUSIC CULTURE LESSONS (International Conference on Educational Discoveries and Humanities, 2025)
This article explores the origins, development, and current significance of the Kashgar rubab, one of the national musical instruments. It also discusses presidential decrees related to the development of national music and instruments.